Factors affecting frequency of child maltreatment in South Korea. (7th February 2022) - Park, Jisun; Cho, Joon Tag
Abstract: A substantial proportion of children suffer multiple episodes of maltreatment over a prolonged period. The cumulative risk of maltreatment is critical to understanding both the nature and effects of victimisation. However, limited studies have investigated the frequency of child maltreatment and the factors influencing its recurrence. This study explored detailed characteristics of non‐sexual child maltreatment in South Korea and determined the factors predicting multiple incidents of child maltreatment using data from investigation and trial records of child maltreatment‐related cases from 2010 to 2015. Based on 440 such cases, the authors examined the characteristics of victims and perpetrators and the features of maltreatment employing the ordered logit model analysis. Child maltreatment was more frequent among children living with the perpetrator and those living with stepparents. The higher the age of the victim, the more frequent the maltreatment. Child maltreatment was also more frequent when the offender was a female. Among the types of maltreatment, emotional abuse and neglect were the most frequent forms of child maltreatment. By identifying various factors influencing the frequency of child maltreatment, the findings can contribute towards protecting children from ongoing maltreatment. Key Practitioner Messages Practitioners need to understand where and how child maltreatment is occurring, so that they may introduce effective interventions. The frequency of child maltreatment rose significantly when the victims lived with a stepparent and when the case involved emotional abuse and neglect. It is imperative to prevent damage to children from ongoing emotional abuse and neglect, especially since it is mostly overlooked compared to physical abuse.